Death Anxiety, Religiosity and Culture: Implications for Therapeutic Process and Future Research - Pandya, Apurva-kumar (Religions, 2021)
Death anxiety is a common phenomenon that humans experience. It is multidimensional. There has been an upsurged interest around the discussion on death anxiety across the globe, however, much of the literature focuses on the concept of death anxiety, religiosity, and its role in mental health conditions. Further, studies on death anxiety are scattered and at times disconnected. It is important to review existing literature to get an overview of the current direction in research and understand its relevance to facilitate therapeutic processes. In this scoping review, literature was searched in databases such as PubMed, Scopus, and PsychINFO using key words such as “death anxiety”, “fear of death”, religion”, “culture”, and “psychopathology” combined with Boolean operators to narrow down the search results. The initial search yielded 614 records, of which 546 records were removed based on title review (363), abstract review (94), and full-text review (89). Finally, 68 articles were appraised, narratively synthesized, and thematically presented. Major themes revealed in the literature were theoretical frameworks of death anxiety, religiosity, universality, psychological effects of death anxiety, psychopathology, and religious coping strategies. There is a need to assess client’s death anxiety and address them using religious rituals and coping mechanisms.